IMPLEMENTASI EDUPREUNEURSHIP DALAM PEMBENTUKAN KARAKTER SEKOLAH UNGGUL - Badrut Tamam; Akhmad Muadin (Ulumuna: Jurnal Studi Keilsman, 2019)
"Implementation of Edupreuneurship in the Formation of Excellent School Characters (Multisitus Study at the Fastabiqul Khairat Foundation and the Bunga Bangsa Samarinda Foundation). This study aims to determine 1) What are the forms of edupreneurship formulation as stated in the strategic plan at the Fastabiqul Khairat Samarinda Foundation and the Bunga Bangsa Samarinda Foundation. 2) To find out how the Implementation of Edupreneurship Foundation Fastabiqul Khairat Samarinda and Samarinda Flower Foundation. The results of the study show that to realize the vision and mission of the educational institutions the two foundations always emphasize the synergy between the elements of the school. Principals, teachers, employees, students as well as parents of students committed in one synergy for the best education for their children. The implementation of edupreneurship in realizing superior school character in the Fastabiqul Khairat Foundation and Bunga Bangsa Samarinda is done by building a commitment to provide the best service to students and parents of students. The implementation of edupreneurship in realizing the character of superior schools in the two leading educational foundations in Samarinda is done in a conscious and systematic way by creating an atmosphere of conscious talent and interest in exploring the potential of students so that educators can adjust to the learning styles of their students. The implementation of edupreneurship in realizing the character of a superior school is done by theorizing and direct practice through the bazaar, business center (school canteen) or bazaar at the classroom level